2020
DOI: 10.1037/trm0000211
|View full text |Cite
|
Sign up to set email alerts
|

Increased empathy and helping behavior toward the mother in daughters of Holocaust survivors.

Abstract: The present study investigated whether prosocial propensities displayed by adult daughters of elderly Holocaust child survivors in a nonclinical/nonselect sample were more pronounced than those in a closely matched comparison group with no Holocaust background. The sample consisted of 78 participants: 42 adult daughters of Holocaust child survivors and 36 women with no Holocaust background in the family. Adult daughters of Holocaust child survivors exhibited elevated physical/medical care and pragmatic help co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 47 publications
0
4
0
Order By: Relevance
“…As caregivers to their older adult parents, OHS provide elevated levels of instrumental help relative to comparisons (Alkalay et al, 2020) and express intense dedication, caregiver stress, and guilt for not doing enough to protect parents from further pain in late life (Shrira et al, 2019). Social distancing prevented OHS from visiting the parents, and protecting parents who reside in nursing homes has been especially challenging due to public health restrictions.…”
Section: Psychological Distress In Offspring Of Holocaust Survivorsmentioning
confidence: 99%
“…As caregivers to their older adult parents, OHS provide elevated levels of instrumental help relative to comparisons (Alkalay et al, 2020) and express intense dedication, caregiver stress, and guilt for not doing enough to protect parents from further pain in late life (Shrira et al, 2019). Social distancing prevented OHS from visiting the parents, and protecting parents who reside in nursing homes has been especially challenging due to public health restrictions.…”
Section: Psychological Distress In Offspring Of Holocaust Survivorsmentioning
confidence: 99%
“…One of these studies reported an association between adjusted and open communication and fewer difficulties in the relationship between survivors and their children (Trachtenberg & Davis, 1978). Similarly, a recent study showed that daughters who had more factual knowledge about their mothers' experiences in the Holocaust exhibited more empathetic responses to their mothers (Alkalay et al, 2019).…”
Section: Introductionmentioning
confidence: 93%
“…With that major caveat in place, we can point out that there is some evidence that PTG is "transmissible" to close others, and even to larger groups and social systems [66,103]. For example, life partners, siblings and/or caregivers of cancer patients or cancer survivors have reported PTG in various studies [104][105][106][107].…”
Section: Growth From One To Manymentioning
confidence: 99%